Chronic beetroot juice supplementation attenuates neuromuscular fatigue etiology during simulated soccer match play - Daab, W.; Zghal, F.; Nassis, G. P.; Rebai, H.; Moalla, W.; Bouzid, M. A. (Applied Physiology, Nutrition, and Metabolism, 2024)
The aim of the present study was to assess the effect of beetroot juice supplementation (BEET) on neuromuscular fatigue etiology during simulated soccer match play. In a randomized, double-blind, crossover design, 13 soccer players completed the Loughborough Intermittent Shuttle Test (LIST). Players received either BEET (2×150 mL; ~8 mmol/L nitrate) or placebo (PLA) for 7 days (6 days prior to the experimental session and on the day of trial, 2 h before LIST). Neuromuscular assessments were performed at baseline, 45 min (half time: HT), and 90 min (full time: FT) following LIST. Maximal voluntary contraction (MVC) and twitch responses, delivered through electrical femoral nerve stimulation, were used to assess peripheral (quadriceps resting twitch force Qtw,pot) and central fatigue (voluntary activation, VA). Compared with baseline, MVC Qtw,pot and VA values decreased in PLA and BEET conditions at HT and FT (P < 0.05). Compared with PLA, the decrease in MVC and Qtw,pot was significantly attenuated with BEET at HT and FT (P < 0.001). Likewise, BEET attenuated the decrease in VA at HT (P < 0.001, d = 1.3) and FT (P < 0.001, d = 1.5) compared with the PLA condition. Chronic beetroot juice supplementation attenuates neuromuscular fatigue development during simulated soccer matches, and this is due to both central and peripheral factors. Consequently, chronic beetroot may optimize physical performance.